ANALISIS PERUBAHAN GAYA HIDUP REMAJA ERA PANDEMI COVID-19 DALAM PERSPEKTIF SOSIOLOGI BUDAYA (STUDI KASUS DI DESA TLUWE KABUPATEN TUBAN) - Dwi Maulita Laelatul Kasanah (Universitas Nahdlatul Ulama Sunan Giri, 2022)
This study aims to describe how the lifestyle changes of teenagers inTluwe Village,Tuban Regency during the Covid-19 pandemic from the perspectiveof cultural sociology. This research was conducted at a location in Tluwe Village,Tuban Regency. This study uses qualitative methods to solve the problems thatoccur. The data collection technique used by the researcher is from the results ofin-depth interviews and observations, as well as documentation in the form of thetext. This research was conducted in 2021. The research subjects weredetermined by sampling. The data analysis technique uses various stages, namely,data reduction, data presentation, conclusion drawing and then the data isanalyzed from a cultural perspective according to Clifford Geertz. The resultsshowed that many teenagers experienced changes due to the pandemic. Thechanges that occurred began with the existence of a policy from the governmentthat required all its people to implement and comply with health protocols. Fromthis policy, it creates habits in teenagers in Tluwe Village, thereby causingchanges in the behavior of teenagers.